Does a Diocotron Effect Exist in Magnetrons? - Moshchenko, I. O.; Nikitenko, O. M. (My University, 2022)
In this article magnetron model has been developed for explanation why the electron beam had wavelike form before oscilation stage. As well known in crossed-field devices electrons move by cycloid-like trajectories. In accordance with the diocotron effect electron beam form has wavelike form because interaction between RF wave and electron beam. But at preoscillation stage we had the same electron beam form in magnetron both planar and cylindrical. Such form we explained by space periodical distribution of an electrostatic potential distribution.
Keywords: magnetron; electrostatic potential distribution; electron beam; wavelike form; diocotron effect